MUHAMMADIYAH TAJDID MOVEMENT IN INDUSTRIAL ERA 4.0 - Sari, Nur Indah; Elihami, Elihami (Al-Mirah: Jurnal Pendidikan Islam, 2020)
The challenges faced by Muhammadiyah in the Industrial 4.0 era were strengthening economic, Islamic, cultural and political integration, and various other elements even though the continuity between several components was not optimal. Without Muhammadiyah's renewal efforts in the Industrial 4.0 era which included a strategy of renewing the education movement that it has been engaged in and various other movements, recognizing contemporary methods and approaches to Islamic and Islamic studies and other variants, being inclusive towards the development of experience and knowledge of the younger generation, open dialogue between culture and religion at the grassroots, and so on.